Injectable hyaluronic acid/oxidized chitosan hydrogels with hypochlorous acid released for instant disinfection and antibacterial effects - Chen, Han; Liao, Ran; Du, Qianqian; Li, Cong; Xiao, Xiufeng; Shan, Yongqi (Frontiers in Materials, 2022)
Bacterial infections of wounds significantly increase the occurrence of complications, which have become a public health problem and pose a serious threat to human health. Therefore, an ideal wound dressing should not only possess suitable mechanical strength and a moist environment, but also instant disinfection and antibacterial properties. Owing to their high water content and permeability, hydrogels have great potential for the application in wound dressing. In this study, we developed an injectable hyaluronic acid (HA)/oxidized chitosan (OCS) hydrogel with good biocompatibility, self-healing, and tissue adhesive properties. Moreover, the slow release of micro hypochlorous acid (HClO), which is a common bactericide during hydrogel formation, can lead to instant disinfection; and the positive charge of OCS in this hydrogel can achieve a sustainable antibacterial effect. Thus, this hydrogel is a promising wound dressing material in clinical treatments.